Study on influencing factors and prediction model of strength and compression index of sandy silt on bank under freeze–thaw cycles - Zhen Yang; Xianyou Mou; Hao Li; Honglan Ji; Yuxin Mao; Hongze Song (Scientific Reports)
Abstract The Inner Mongolia section of the Yellow River is a seasonal frozen soil area, where the freeze–thaw effect can alter soil strength and compressibility, affecting bank stability. This study takes the banks sandy silt of the Inner Mongolia section of the Yellow River as the research object. It systematically investigates the relationship between shear strength parameters and compression index of sandy silt and the initial dry density, water content, and freeze–thaw cycles of the soil. It analyzes the order and significance of influencing factors, establishes prediction models of shear strength and compression index, and evaluates the effects of freeze–thaw cycles on soil cohesion and shear strength. The results show that the shear strength index of sandy silt is proportional to changes in initial dry density and inversely proportional to changes in water content. After 10 freeze–thaw cycles, the cohesion of the soil decreases by 22.53 to 58.85%, and the shear strength decreases by 22.67 to 58.91%. The internal friction angle is less affected by freeze–thaw and tends to be stable overall. The smaller the initial dry density and the greater the water content, the greater the compression index and compressibility of the soil, but freeze–thaw has little effect on compression index. The factors affecting sandy silt shear strength and compression index are ranked as dry density > moisture content > freeze–thaw cycles. The stepwise regression model of soil shear strength and compression index based on initial dry density, water content, and freeze–thaw cycles is effective, providing technical guidance for engineering practice.